Student’s Psychology During The Covid-19 Pandemic : A Comparative Study Between Vocational And Technical Training Students - Denden, Mohsen; Alkhalifah, Ahmed (Indonesian Scientific Publication, 2024)
The world has recently suffered from the repercussions of the COVID-19 pandemic, as the number of victims of this epidemic has increased significantly, and people have lost their families and loved ones in a short time. The feeling of inability to face the difficulties resulting from this pandemic had bad repercussions on the mental health of many people, especially those with disabilities, who faced difficulty in continuing their already unstable daily routines. In this work, a comparative study is carried out to determine the impact of the COVID-19 pandemic on the morale of the vocational program students. The study concerns non-disabled students and deaf, hard-of-hearing students. For this, a DASS test was applied to extract the states of stress, anxiety, and depression. A second test called MFT is applied to extract the main causes and effects. The results are surprising since all cases show a negative effect on the part of deaf and hard of hearing compared to other student.